Efficacy and safety of thalidomide in children with monogenic autoinflammatory diseases: a single-center, real-world-evidence study - Caihui Zhang; Zhongxun Yu; Sihao Gao; Mingsheng Ma; Lijuan Gou; Changyan Wang; Lin Wang; Ji Li; Linqing Zhong; Yu Zhou; Wei Wang; Hongmei Song (Pediatric Rheumatology Online Journal, 2023)
Abstract Background Monogenic autoinflammatory diseases (AIDs) are rare inflammatory diseases caused by genetic variants. The pathogenesis is complex and treatment options are limited. This study aimed to describe the safety and efficacy of thalidomide in the treatment of monogenic AIDs. Methods This was a single-center, single-arm, real-world study. From September 2016 to August 2021, patients with monogenic AIDs who met the inclusion and exclusion criteria were given thalidomide for 12 months. There was a 3-month run-in period before dosing. The efficacy and adverse events were evaluated and recorded every 3 months. After 3 and 12 months of thalidomide treatment, clinical manifestations, disease activity score, inflammatory markers, and background medication adjustments were compared with baseline for efficacy analyses. Results A total of 16 patients entered this study, including 3 with Aicardi-Goutières syndrome (AGS), 4 Blau syndrome, 2 chronic infantile neurologic cutaneous articular syndrome (CINCA), 2 A20 haploinsufficiency (HA20), 1 adenosine deaminase 2 deficiency(DADA2), 1 familial Mediterranean fever (FMF),1 tumor necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS), 1 PLCγ2-associated antibody deficiency and immune dysregulation (PLAID), and 1 stimulator of interferon genes-associated vasculopathy with onset in infancy(SAVI). The efficacy rate in the 16 patients after 3-month and 12-month thalidomide treatment in patients was 56.3%. Twelve patients completed the study, the fever improved in all of them, rash improved in 7 patients, and 5 patients stopped using glucocorticoids or other immunosuppressive agents. C-reactive protein was normal in 8 patients and erythrocyte sedimentation rate was normal in 11 patients. Anorexia and nausea occurred in 2 cases, with no other reported drug-related adverse reactions. Conclusion The largest cohort of monogenic AIDs with the treatment of thalidomide demonstrated that thalidomide can help reduce disease activity and inflammation, reduce the dosage of glucocorticoids, and improve clinical outcomes. Thalidomide is relatively safe in monogenic AIDs.